Dejavniki bralne pismenosti in družinskega branja v otrokovem predšolskem obdobju - Haramija, Dragica (Jezik in slovstvo, 2018)
Based on the results of two separate surveys regarding reading literacy in the preschool period, we conducted an analysis of various research surveys on reading literacy and family reading and produced an improved platform for the development of reading literacy and family reading in the preschool period. We included the results of a research project entitled Cultural and Systematic Factors of Reading Literacy in Slovenia, and of a research and development project on family literacy entitled Hugged by Words. The results were analysed in the light of key competences for the twenty-first century (based on eight key competences for lifelong learning), the guidelines on emergent literacy as set out within the White Paper on Education (2011), and the proposal of a National Literacy Strategy (2017). The factors in family literacy development are system-related and cultural. One of the key system-related factors is preschool education, which has a tremendous impact on family literacy, as the current Curriculum for Preschool (1999) establishes the foundation for the understanding of different activities in the kindergarten, focusing above all on recognising the fact that literacy extends to all areas of activity (movement, language, art, society, nature, mathematics).
Keywords: bralna pismenost; družinska pismenost; kulturni dejavniki; predšolsko izobraževanje; sistemski dejavniki